Effect of mixed resistance and endurance training on body composition, cardio risk factors and fitness in inactive male Iranian students - Esmaelzadeh Toloee, Mohammad Reza (2011)
Several studies have shown a positive association between regular physical activity and reduction of cardiovascular diseases. However, the relationship among the types of physical activity and risk factors (such as; triglyceride, TG, LDL, HDL, CPR and IL-6 levels) in inactive young people remain unclear. The objective of this research was to examine the effects of mixed resistance and endurance training on body composition, cardio risk factors and fitness in inactive male Iranian students. Fifty four healthy inactive students aged 18-24 yrs (inactive men) were assigned into four groups: 1) mixed resistance and endurance training (MTG) (n=13), 2) endurance training (ETG) (n=13), 3) resistance training (RTG) (n=14) or 4) control (CG) (n=14). All the training groups (MTG, ETG and RTG) performed the special exercise program assigned to them until 8 weeks (3 days per week). The MTG performed resistance training which consists of the following exercises: l) the leg press 2) leg extension, 3) seated leg curl 4) abdominal 5) chest press 6) seated row with 50% to 80% 1RM (three sets of 10-12 repetition). This was followed by 30-minutes of endurance training (jogging, fartlek and running) with 60% -85% HRmax. The ETG participated in aerobic exercise training protocol (jogging and running in track and fartlek with %55-%85 HRmax). The RTG performed resistance training program which consists of the following exercises: 1) leg press, 2) leg extension, 3) seated leg curl, 4) back extension, 5) abdominal, 6) chest press, 7)seated row, 8) lat pull down, and 9) triceps pushdown with 50% to 80% 1RM (threesets of 10-12 repetition). The CG continued the same routine activity that they had used prior to becoming a study participant. Pre and post tests measures included:VO2max, one repetition maximum, weight, waist and hip circumferences, body composition, blood cardio risk factors (LDL, VLDL, HDL, Triglyceride,Cholesterol, glucose, insulin, CRP and IL-6). Significant improvements were reported for variables such as High Density Lipoprotein (p=0.01), VO2max, skeletal muscle mass (p=0.001), and upper and lower body strength (p<0.05) among the MTG subjects. Better blood profiles were also observed in this group with a significant decrease in HOMA-ir (p=0.02) and Interleukin-6 (p=0.01). The MTG was also displayed to have significant reduction in body fat percentage (p=0.001). For the ETG, the variables that showed significant improvement were HDL (p=0.03), fasting blood glucose (p=0.03), interleukin-6 (p=0.01), VO2 max (p=0.001), body fat percentage (p=0.001), and Heart Rate (HR) during rest, exercise, and recovery (p<0.05). The RTG showed the least improvement as compared to the MTG and ETG. The variables of this group that showed significant improvement were HOMA-ir (p=0.01), insulin level (p=0.04), skeletal muscle mass (p=0.01), and upper and lower body strength (p<0.01). The results of this study show that mixed resistance and endurance training improves some cardio risk factors, cardiorespiratory fitness, upper and lower body strength, and body composition in healthy inactive students. While resistance training significantly improved upper and lower body strength only and endurance training significantly improved cardio risk factors, cardiorespiratory fitness.